Professional approach and suicidal behavior in Primary Health Care. - Negrão, Ana Iria de Oliveira; Silva, Thiago Domingos da; Frangonari, Tatiane Ferrari; Horta, Ana Lucia de Moraes (Acta Paulista de Enfermagem, 2024)
Objective: To describe the professional approach to people with suicidal behavior in Primary Health Care and its associations with the sociodemographic, educational and occupational variables of health workers. Methods: Cross-sectional study of 192 health professionals from 20 Basic Health Units in a municipality in greater São Paulo. A questionnaire for sociodemographic, educational and occupational characterization was applied, as well as the instrument for Evaluating Professional's Assistance to People with Suicidal Behavior. The results were presented using measures of central tendency and dispersion, and parametric and non-parametric tests were used in the analysis, considering the nature of the variables. A significance level of 5% was adopted. Results: There was a predominance of females, average age of 43.27 years, higher education, and average working time of 10.71 years. The higher scores were reached in the Professional Sensibility and Knowledge/Abilities domains. Lower scores were obtained for Professional Experience and Organization of the Care Network, demonstrating frailty in the professional performance and in network coordination needed in the approach to suicidal behavior. Age, working time in the unit and the frequency of treatment of populations at risk for suicidal behavior were associated with scores in Professional Sensibility, Experience and Knowledge/Abilities. Conclusion: Sensibility, knowledge and abilities of Primary Care health professionals contribute to the approach to suicidal behavior, associated with occupational and educational characteristics. Professional experience and Organization of the care network reveal the weaknesses in the coordination necessary to approach suicidal behavior, indicating paths for training and work in health.